Corticosteroid Pulse Therapy for Graves' Ophthalmopathy Reduces the Relapse Rate of Graves' Hyperthyroidism - Le Moli, Rosario; Malandrino, Pasqualino; Russo, Marco; Lo Giudice, Fabrizio; Frasca, Francesco; Belfiore, Antonino; Vigneri, Riccardo (Frontiers in Endocrinology, 2020)
Background: A course of anti-thyroid drugs (ATD) is the most common first line treatment for Graves' hyperthyroidism. However, hyperthyroidism relapse is frequent (30–70%). Due to the autoimmune nature of Graves' disease, the immunosuppressive treatment used for active Graves' orbitopathy (GO) may reduce the relapses after ATD discontinuation. Objective: To evaluate the recurrence rate in Graves' patients who, in addition to standard ATD, were treated or not treated with parenteral methylprednisolone (MPDS) for GO. Methods: Single-center retrospective study in a continuous series of 162 newly diagnosed Graves' patients, with or without GO, all gone into remission and followed-up until hyperthyroidism recurrence or at least 4 years after ATD discontinuation. Patients with moderate-severe active GO underwent middle dose MPDS treatment according to the EuGoGo guidelines. Cox proportional-hazard model was used to comparatively evaluate the risk of recurrence and the predictive factors in patients treated or not treated with MPDS pulse therapy. Results: MPDS treatment was the most significant factor that independently correlated with a reduced risk of hyperthyroidism relapse (HR = 0.53, 95% C.I. = 0.31–0.89). FT3 and female sex were also independent protective factors, while age almost reached the significance level, p = 0.062. The efficacy of MPDS was very high in patients aged <40 years (42.1% decrease in relapses, p < 0.01) but it was not significant in older patients. Discussion: Our study found that after ATD discontinuation the frequency of Graves' hyperthyroidism relapse was reduced in patients treated with MPDS pulse therapy for GO. This effect was more marked in young patients.